Counselling of path_BRCA carriers who are considering risk-reducing oophorectomy. Issue 1 (March 2023) - Manley, Kristyn; Ryan, Neil; Jenner, Abigail; Newton, Claire; Hillard, Timothy
Path_ BRCA 1/2 increases a woman's lifetime risk of breast and ovarian cancer. Interventions can be offered which manage cancer risk; annual breast screening from age 30, chemoprevention and, once a woman's family is complete, risk-reducing surgery. The latter is the most effective method of reducing cancer in path_ BRCA carriers; salpingo-oophorectomy reduces breast and ovarian cancer, respectively, by up to 50% and 95%. Factors affecting a woman's decision to undergo risk-reducing surgery are complex; dominant factors include risks of surgery, effect on cancer outcomes and menopausal sequelae. Specific information relating to hormone replacement and non-hormonal alternatives are an important consideration for women but, are often overlooked. Informative counselling is required to enable satisfaction with the chosen intervention whilst improving survival outcomes. This review paper outlines the current data pertaining to these decision-making factors and provides a proforma to enable effective counselling.